2021
DOI: 10.3390/ma14143828
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Radiographic, and Histomorphometric Evaluation of a Vertical Ridge Augmentation Procedure Using a Titanium-Reinforced Microporous Expanded Polytetrafluoroethylene Membrane: A Prospective Case Series with 1-Year Follow-Up

Abstract: Vertical ridge augmentation for long-term implant stability is difficult in severely resorbed areas. We examined the clinical, radiological, and histological outcomes of guided-bone regeneration using novel titanium-reinforced microporous expanded polytetrafluoroethylene (MP-ePTFE) membranes. Eighteen patients who underwent implant placement using a staged approach were enrolled (period: 2018–2019). Vertical ridge augmentation was performed in areas with vertical bone defects ≥ 4 mm. Twenty-six implant fixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In another study by the same research group, expanded polytetrafluoroethylene membranes combined with simultaneous implant placement were able to regenerate 2.94 ± 1.15 mm (89.3 ± 64.2%), 3.27 ± 0.88 mm (130 ± 40.7%), and 3.95 ± 1.79 mm (116 ± 51%) of the defect when they were used without graft, in combination with demineralized freeze‐dried bone allograft, or in combination with autologous graft, respectively 26 . Furthermore, nonresorbable membranes were used in combination with alloplastic materials, 42 xenografts, 43,44 allografts, 26,41,45,46 autologous grafts, 23,26,41,45–48 and combinations thereof 38,45,49–56 yielding similar results with percentage bone gain ranging between 62% and 139%. Regarding the time of implant placement, both simultaneous 23,26,38,41,42,44,45,48,52 and staged approaches 23,41,43,45–47,49–56 were shown to be effective in yielding vertical regeneration.…”
Section: Techniques On Vertical Ridge Augmentationmentioning
confidence: 91%
See 4 more Smart Citations
“…In another study by the same research group, expanded polytetrafluoroethylene membranes combined with simultaneous implant placement were able to regenerate 2.94 ± 1.15 mm (89.3 ± 64.2%), 3.27 ± 0.88 mm (130 ± 40.7%), and 3.95 ± 1.79 mm (116 ± 51%) of the defect when they were used without graft, in combination with demineralized freeze‐dried bone allograft, or in combination with autologous graft, respectively 26 . Furthermore, nonresorbable membranes were used in combination with alloplastic materials, 42 xenografts, 43,44 allografts, 26,41,45,46 autologous grafts, 23,26,41,45–48 and combinations thereof 38,45,49–56 yielding similar results with percentage bone gain ranging between 62% and 139%. Regarding the time of implant placement, both simultaneous 23,26,38,41,42,44,45,48,52 and staged approaches 23,41,43,45–47,49–56 were shown to be effective in yielding vertical regeneration.…”
Section: Techniques On Vertical Ridge Augmentationmentioning
confidence: 91%
“…Nevertheless, even though the occurrence of membrane exposure is rather frequent (approximately 12%), the percentages of failures reported in the literature are low. 26,41,43,45,46,48,50,54,55,[58][59][60]63,65,66 Simion et al, 26 using expanded polytetrafluoroethylene membranes, achieved regenerations of roughly 57% and 128% of the original defect in exposed and nonexposed sites, respectively. Similarly, Beitlitum et al, 58 using a cross-linked collagen membrane, found that membrane exposure led to approximately 50% less bone regeneration.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
See 3 more Smart Citations